2006
DOI: 10.1097/01.brs.0000240704.42264.c4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1-Stage Versus 2-Stage Anterior and Posterior Spinal Fusion for Severe and Rigid Idiopathic Scoliosis–A Randomized Prospective Study

Abstract: A comparison of 1-stage versus 2-stage fusion in treating rigid thoracic curves in AIS did not show significant differences in safety or efficacy but did demonstrate significant difference in length of stay and patient cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…Scoliosis with a high angular value can be treated by anterior approach alone according to Shen et al, 11 who described their study in which they performed anterior release associated with instrumentation and fusion in 12 patients with an average Cobb of 98.5°, obtaining 59.5% correction. Anterior release via thoracoscopy prior to posterior arthrodesis has been described as being less invasive and optimizing clinical results, but the technical difficulty of this procedure in patients with severe deformity of the thoracic cage is a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis with a high angular value can be treated by anterior approach alone according to Shen et al, 11 who described their study in which they performed anterior release associated with instrumentation and fusion in 12 patients with an average Cobb of 98.5°, obtaining 59.5% correction. Anterior release via thoracoscopy prior to posterior arthrodesis has been described as being less invasive and optimizing clinical results, but the technical difficulty of this procedure in patients with severe deformity of the thoracic cage is a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…The combined anterior and posterior procedure was performed in one-or two-stage surgery by different authors with different outcomes. Shufflebarger et al [2] found that a reduction in hospital stay and operating time led to fewer complications, and better correction in the continuous group compared with the staged one; more recently, Shen et al [3] concluded that there was no significant difference in the safety or efficacy between the one-or two-stage groups. Additional anterior surgery requires increased time for the general anesthesia and may have a negative impact on pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…The combined anterior and posterior procedure was performed in 1-or 2-stage surgery according to different authors with different outcomes. Shufflebarger et al [46] found decreased hospital stay and operating time, fewer complications, and better correction in the continuous group compared to the staged group; more recently Shen et al [45] concluded that there was no significant difference in safety or efficacy between the 1-or 2-stage groups.…”
Section: Introductionmentioning
confidence: 99%